2019
DOI: 10.21511/ppm.17(2).2019.03
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory changes and reporting quality: the moderating role of firm characteristics

Abstract: The objective of this study is to investigate the effect of regulatory changes on financial reporting quality and audit fees and to further test whether this effect was moderated by firm characteristics (i.e. abnormal audit fees, political connections and overlapping directorship) in Nigeria. This study utilized the data of 90 companies listed on the Nigerian stock exchange over the period 2008–2013. Using Generalized Method of Moments (GMM) technique that takes into account the endogeneity nature of financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…The present study argues that the various regulatory reforms in Nigeria will affect auditors' pricing decisions since the various regulatory changes will improve the financial reporting architecture. The findings of Abdulmalik and CheAhmed (2019) confirm the assertion of an improvement in financial reporting quality. These authors reported that the regulatory changes arising from the creation of FRCN in 2011 and the adoption of IFRS in 2013 have improved the financial reporting quality in Nigeria.…”
Section: Hypothesis Developmentsupporting
confidence: 74%
See 1 more Smart Citation
“…The present study argues that the various regulatory reforms in Nigeria will affect auditors' pricing decisions since the various regulatory changes will improve the financial reporting architecture. The findings of Abdulmalik and CheAhmed (2019) confirm the assertion of an improvement in financial reporting quality. These authors reported that the regulatory changes arising from the creation of FRCN in 2011 and the adoption of IFRS in 2013 have improved the financial reporting quality in Nigeria.…”
Section: Hypothesis Developmentsupporting
confidence: 74%
“…Hence, skill transformation might be required to keep abreast of the changes on the part of an auditor. For example, the global move from precise to less precise accounting standards requires much professional judgement (Abdulmalik and CheAhmed, 2019). Regulatory reform will necessitate the deployment of financial resources for retraining to ensure that audit team members possess the skills needed in the new regulatory regime (Lin and Yen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to address the issues surrounding SRQ, the role of the board in terms of corporate governance mechanisms is pertinent, hence the transparency and credibility of corporate reporting bother on effective board in terms of monitoring (MCCG, 2017;Osazuwa et al, 2017). Although, corporate scandals like Enron, WorldCom and others like Sime Darby, Kenmark Ltd, and Linear Corporation in Malaysia, were attributed to corporate governance failure which has caused stakeholders much concern in terms of the credibility of corporate reporting (Abdulmalik & Che-Ahmad, 2019;Ofoegbu et al, 2018). This situation has informed several reforms in corporate governance worldwide and specifically in Malaysia (Abdulmalik & Che-Ahmad, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although, corporate scandals like Enron, WorldCom and others like Sime Darby, Kenmark Ltd, and Linear Corporation in Malaysia, were attributed to corporate governance failure which has caused stakeholders much concern in terms of the credibility of corporate reporting (Abdulmalik & Che-Ahmad, 2019;Ofoegbu et al, 2018). This situation has informed several reforms in corporate governance worldwide and specifically in Malaysia (Abdulmalik & Che-Ahmad, 2019). For example, the Revised Malaysian Code of Corporate Governance (MCCG) 2017 and the revised Malaysian Sustainability Reporting Guide (SRG) in 2018 (Bursa Malaysia, , 2018.…”
Section: Introductionmentioning
confidence: 99%